Heat 2 : a novel - Mann, Michael; Gardiner, Meg (HarperCollinsPublishers, 2022)
One day after the end of Heat, Chris Shiherlis (Val Kilmer) is holed up in Koreatown, wounded, half delirious, and desperately trying to escape LA. Hunting him is LAPD detective Vincent Hanna (Al Pacino). Hours earlier, Hanna killed Shiherlis's brother in arms Neil McCauley (De Niro) in a gunfight under the strobe lights at the foot of an LAX runway. Now Hanna's determined to capture or kill Shiherlis, the last survivor of McCauley's crew, before he ghosts out of the city. In 1988, seven years earlier, McCauley, Shiherlis, and their highline crew are taking scores on the West Coast, the US-Mexican border, and now in Chicago. Driven, daring, they're pulling in money and living vivid lives. And Chicago homicide detective Vincent Hanna - a man unreconciled with his history - is following his calling, the pursuit of armed and dangerous men into the dark and wild places, hunting an ultraviolent gang of home invaders. Meanwhile, the fallout from McCauley's scores and Hanna's pursuit cause unexpected repercussions in a parallel narrative, driving through the years following Heat.
Keywords: Shiherlis, Chris : (fiktiivinen hahmo); Hanna, Vincent : (fiktiivinen hahmo); järjestäytynyt rikollisuus; menneisyys; rikostutkijat; Los Angeles; Yhdysvallat